Translational Medicine and Patient Safety in Europe: TRANSFoRm—Architecture for the Learning Health System in Europe. (11th October 2015) - Delaney, Brendan C.; Curcin, Vasa; Andreasson, Anna; Arvanitis, Theodoros N.; Bastiaens, Hilde; Corrigan, Derek; Ethier, Jean-Francois; Kostopoulou, Olga; Kuchinke, Wolfgang; McGilchrist, Mark; Royen, Paul van; Wagner, Peter
Abstract : The Learning Health System (LHS) describes linking routine healthcare systems directly with both research translation and knowledge translation as an extension of the evidence-based medicine paradigm, taking advantage of the ubiquitous use of electronic health record (EHR) systems. TRANSFoRm is an EU FP7 project that seeks to develop an infrastructure for the LHS in European primary care. Methods . The project is based on three clinical use cases, a genotype-phenotype study in diabetes, a randomised controlled trial with gastroesophageal reflux disease, and a diagnostic decision support system for chest pain, abdominal pain, and shortness of breath. Results . Four models were developed (clinical research, clinical data, provenance, and diagnosis) that form the basis of the projects approach to interoperability. These models are maintained as ontologies with binding of terms to define precise data elements. CDISC ODM and SDM standards are extended using an archetype approach to enable a two-level model of individual data elements, representing both research content and clinical content. Separate configurations of the TRANSFoRm tools serve each use case. Conclusions. The project has been successful in using ontologies and archetypes to develop a highly flexible solution to the problem of heterogeneity of data sources presented by the LHS.